Environmental and Social Effects of Stone Quarrying in Bangladesh: A Study in the Khasi People Area in Sylhet - Mohammad Jahirul Hoque; Hajera Aktar (Space and Culture, India, 2022)
This study investigates how the unregulated and unscientific manner of stone quarrying in Bangladesh degrades the environment and affects the life and livelihoods of the local people. The recent countrywide construction boom and infrastructural development kept the GDP growth constant in Bangladesh. This construction boom generates colossal demand for stones, and the Sylhet region is its major supplier. Although there are laws and legal mechanisms to regulate stone quarrying in the country, the miners do not follow these. This study found that the local Khasi people of the stone quarrying area have been experiencing systematic and forcible dispossession due to merging their lands into stone quarrying sites. These people are the victims of different forms of pollution due to unregulated stone quarrying. And the area has been experiencing a social transformation because of the settling of the people of the mainstream Bengali community from the poverty porn areas of the country to sustain their life by managing their livelihoods by working in the stone quarries. The study also explores how the lack of monitoring and corruption of the state and non-state actors in the stone quarrying sectors degraded the environment and transformed society in the last decades.